2016
DOI: 10.3109/09537104.2016.1143919
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic implications of mean platelet volume on short- and long-term outcomes among patients with non-ST-segment elevation myocardial infarction treated with percutaneous coronary intervention: A single-center large observational study

Abstract: In patients with NSTEMI treated with PCI, a high MPV value was associated with a significantly increased incidence of long-term adverse events, particularly for all-cause mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
1
2

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(42 citation statements)
references
References 30 publications
0
39
1
2
Order By: Relevance
“…Platelet volume indices are indicator of platelet activation and play an important role in the pathophysiology of cardiovascular diseases 16, 17. In the study, we found that patients with OSA have higher MPV and platelet large cell ratio values (Figure 1A and 1B).…”
Section: Resultsmentioning
confidence: 76%
See 2 more Smart Citations
“…Platelet volume indices are indicator of platelet activation and play an important role in the pathophysiology of cardiovascular diseases 16, 17. In the study, we found that patients with OSA have higher MPV and platelet large cell ratio values (Figure 1A and 1B).…”
Section: Resultsmentioning
confidence: 76%
“…Recently, Wasilewski et al have reported that all‐cause mortality is 1.5‐fold higher in non‐ST‐segment elevation myocardial infarction patients with high MPV values 17. In earlier studies, MPV and PDW were found to be significantly higher in patients with severe OSA when compared with control subjects 23, 24.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Large platelets have denser granules containing mediators that play a role in inflammation, atherosclerosis, and eventually cardiac syndromes. Higher MPV is associated with increased mortality after both ST segment elevation myocardial infarction (STEMI) and non-STEMI [7,8]. Higher MPV correlates with the reperfusion failure in STEMI [8,9].…”
Section: Discussionmentioning
confidence: 99%
“…[29,31]. После публикации последне-го метаанализа в 2015 г. появилось еще не-сколько работ, подтверждающих прогностичес-кую значимость СОТ у больных с ОКС [32,41,42]. По крайней мере, в одном исследовании была выявлена корреляция СОТ с риском тромбо-зов после ЧКВ у больных со стабильной ИБС [43].…”
Section: средний объем тромбоцитов у больных с сердечно-сосудистыми пunclassified